A study of the vapour–liquid equilibrium of CO2 in mixed solutions of potassium carbonate and potassium glycinate. (May 2015) - Lee, Andrew; Wolf, Moritz; Kromer, Niko; Mumford, Kathryn A.; Nicholas, Nathan Johann; Kentish, Sandra E.; Stevens, Geoff W.
Highlights: VLE of potassium carbonate and glycinate with CO2 was studied at 50, 60 and 70 °C. Glycinate acted as an additional mode of CO2 storage forming glycine carbamate. Glycine carbamate concentrate decreased at higher temperatures indicating that it can be regenerated. Abstract: The vapour–liquid equilibrium of CO2 above a solution of potassium carbonate and potassium glycinate was studied in a dynamic equilibrium apparatus, with a stationary liquid phase and moving gas phase. The partial pressure of CO2 and liquid phase speciation was measured for solutions containing 4.82 mol potassium carbonate/kg water and 0.64, 1.36, 2.16 and 3.06 mol potassium glycinate/kg water across a range of loadings at temperatures of 50 °C, 60 °C and 70 °C. It was found that the partial pressure of CO2 decreased significantly as the concentration of potassium glycinate increased, indicating that the potassium glycinate was acting as an additional mode of CO2 capture within the solution. This was supported by significant amounts of glycine carbamate observed in the solutions. The partial pressure of CO2 was found to increase with increasing temperature whilst the amount of glycine carbamate decreased, indicating that the solvent can be thermally regenerated.